Novel acetylcholinesterase reactivator K112 and its cholinergic properties - Soukup, O; Kristofikova, Z; Proska, J; Tobin, G; Patocka, J; Marek, J; Jun, D; Fusek, J; Ripova, D; Kuca, K (Biomedicine & pharmacotherapy, 2010)
The oxime reactivator K112 is a member of the new group of xylene linker-containing AChE reactivators. Its cholinergic properties could be of importance at OP poisoning and are not related to the AChE reactivation that has been studied. It has been found that, despite of reactivating potency, this compound has additional effects. These cholinergic effects include a weak inhibition of AChE (IC(50)=43.8 ± 4.88 μM), inhibition of binding to the porcine muscarinic M2 receptor (IC(50)=4.36 μM) and finally, the inhibition of HACU (68.4 ± 9.9%), a key regulatory step in the synthesis of ACh. The inhibition of the binding of (3H)-HC-3 (64.7 ± 4.7%) and the influence on the membrane fluidity have also been observed. Blocking properties of K112 on the muscarinic receptors have been revealed in the in vitro experiment (rat urinary bladder) and in the in vivo experiment (rat heart BPM) as well. All these cholinergic properties could significantly contribute to the antidotal effect of K112 at the poisoning by the organophosphates.
Keywords: Muscle Contraction; Organophosphate Poisoning; synaptozomy; Dose-Response Relationship, Drug; pyridinové sloučeniny; Rats; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; In Vitro Techniques; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; otrava; Protein Binding; potkani Sprague-Dawley; hipokampus; rekombinantní proteiny; svalová kontrakce; Cholinesterase Inhibitors; Rats, Wistar; Urinary Bladder; Oximes; techniky in vitro; močový měchýř; Heart Rate; krysa rodu Rattus; Pyridinium Compounds; otrava organofosfáty; srdeční frekvence; Swine; Muscle, Smooth; Membrane Fluidity; Synaptosomes; zvířata; fluidita membrány; Poisoning; Receptor, Muscarinic M2; receptor muskarinový M2; vazba proteinů; Heart; Rats, Sprague-Dawley; prasata; potkani Wistar; oximy; reaktivátory cholinesterasy; hladké svalstvo; srdce; Recombinant Proteins; Hippocampus; Animals